2016
DOI: 10.3892/mmr.2016.4841
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-let-7f-1 is induced by lycopene and inhibits cell proliferation and triggers apoptosis in prostate cancer

Abstract: Previous studies have suggested that lycopene has cytotoxic effects in a variety of types of human cancer. An improved understanding of the mechanisms underlying the anticancer effects of lycopene may provide novel therapeutic targets for cancer treatment. PC3 cells were treated with different concentrations of lycopene for 24 and 48 h, the level of protein kinase B (AKT2) was detected by reverse transcription‑quantitative polymerase chain reaction (RT‑qPCR) and western blotting. Additionally, the expression l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 36 publications
1
16
0
4
Order By: Relevance
“…The Let-7 family has 10 members in the human genome (Let-7a, let-7b, let-7c, let-7d, let-7e, let-7f, let-7g, let-7i, miR-98, and miR-202 38 ), which are involved in gene regulation and cell adhesion. We found, Let-7f microRNAs were strikingly downregulated in HGDN and eHCC (1 million-fold change) and Let-7g in HCC (358-fold change) with similar reports published in gastric 39 , 40 , prostate 41 , colon 42 , 43 , small cell lung 44 , thyroid 45 , breast 46 , 47 , and hepatocellular cancer 48 , 49 . miR-221, was found to be upregulated in HCC via in silico analysis and has multiple known pathway targets, such as p27Kip1, p53, BMF, PI3K, PTEN, and mTOR 50 .…”
Section: Discussionsupporting
confidence: 89%
“…The Let-7 family has 10 members in the human genome (Let-7a, let-7b, let-7c, let-7d, let-7e, let-7f, let-7g, let-7i, miR-98, and miR-202 38 ), which are involved in gene regulation and cell adhesion. We found, Let-7f microRNAs were strikingly downregulated in HGDN and eHCC (1 million-fold change) and Let-7g in HCC (358-fold change) with similar reports published in gastric 39 , 40 , prostate 41 , colon 42 , 43 , small cell lung 44 , thyroid 45 , breast 46 , 47 , and hepatocellular cancer 48 , 49 . miR-221, was found to be upregulated in HCC via in silico analysis and has multiple known pathway targets, such as p27Kip1, p53, BMF, PI3K, PTEN, and mTOR 50 .…”
Section: Discussionsupporting
confidence: 89%
“…A inclusão do licopeno extraído do tomate e de outras frutas, tais como melancia e goiaba cor-de-rosa, demonstrou ser uma medida efetiva na prevenção e no tratamento do câncer de próstata, principalmente pela vantagem de que o licopeno pode atingir uma concentração muito maior no tecido prostático e garantir o efeito de proteção. 8 Em consonância com o ►Quadro 2, foram encontradas seis publicações com a referida temática.…”
Section: Resultados E Discussõesunclassified
“…Entretanto, estudos adicionais são necessários para a comprovação do uso medicinal do mesmo. 15 Corroborando, Li et al, 8 averiguando os mecanismos subjacentes aos efeitos anticancerígenos do licopeno enquanto alvo terapêutico para o tratamento do câncer, analisaram as células de adenocarcinoma prostático PC3 através de tratamentos em diferentes concentrações de licopeno durante 24 e 48 horas, nos quais o nível de proteína quinase B beta (AKT2) foi detectado por transcrição reversareação em cadeia da polimerase quantitativa, sendo elucidado que o licopeno está envolvido nos efeitos anticancerígenos atuando na inibição da progressão do câncer de próstata. 16 Conclusão O licopeno, por ser um composto natural, tem como principais fontes o tomate e produtos à base do mesmo, melancia e goiaba, conferindo grande capacidade antioxidante, sendo capaz de atingir concentrações bastante elevadas no tecido prostático.…”
Section: Resultados E Discussõesunclassified
“…Similarly, lycopene impedes the proliferation and survival of prostate cancer cells [ 77 ]. It was further shown that let-7f is transcriptionally activated by lycopene and targets Akt2 [ 77 ], suggesting that the status of let-7f and Akt2 can determine the efficiency of lycopene ( Figure 3 and Table 4 ).…”
Section: Tumor-suppressive Mirnas Induced By Phytochemicals Currenmentioning
confidence: 99%